Comparison of the safety and efficacy of triple sequential therapy and transscleral cyclophotocoagulation for neovascular glaucoma in the angle-closure stage - Ying Hong (Nature Portfolio, 2018)
Abstract To compare the efficacy and safety of triple therapy combining intravitreal injection of anti-vascular endothelial growth factor, trabeculectomy, and pan-retinal photocoagulation via binocular indirect ophthalmoscopy, with that of transscleral cyclophotocoagulation (TCP) to treat neovascular glaucoma in the angle-closure stage. Eighteen triple therapy patients and 25 TCP patients between May 2014 and May 2016 were retrospectively analysed. Anterior chamber puncture and anti-VEGF intravitreal injection were performed on the first day of sequential therapy. Trabeculectomy was performed 3–5 d after injection; pan-retinal laser photocoagulation via binocular indirect ophthalmoscopy was initiated 5–7 d later. The IOP of the triple therapy group was lower than that of the TCP group (15.2 ± 2.2 vs. 20.0 ± 8.5 mmHg) and fewer anti-glaucoma drugs were used (0.5 ± 1.0 vs. 0.6 ± 1.0) after treatment. The success rates of the two groups were 89% and 60% respectively (P = 0.032). The visual function of 94% of triple therapy patients was preserved or improved compared to 64% of TCP patients with statistical significance (P = 0.028). No patient in the triple therapy group showed hypotony or eyeball atrophy. Compared to TCP, triple therapy shows higher success rate, fewer complications, and attributes to visual function preservation.